Pengaruh Etos Kerja Dan Sistem Infomasi Manajemen Pegawai (SIMPEG) Terhadap Produktivitas Kerja Pegawai Yang Bekerja Secara WFH Pada Pusat Sains Dan Teknologi Atmosfer (PSTA) Lapan Bandung - Adi Permana Sidik; Sabilla Saberina; Ratih Hadiantini (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2021)
This study aims to determine the effect of work ethic and Employee Management Information System (SIMPEG) and work productivity of employees who work in WFH at the Center for Atmospheric Science and Technology (PSTA) LAPAN Bandung. The method used in this research is descriptive and verification with a quantitative approach. The population used in this study were all employees of the Center for Atmospheric Science and Technology totaling 88 respondents using non-probability sampling techniques, saturated samples. Based on the research results that work ethic is in the low category, Employee Management Information System (SIMPEG) is in the low category and work productivity is in the low category with the magnitude of the influence of work ethic on work productivity by 3%, Employee Management Information System (SIMPEG) on productivity work amounted to 6%, and the effect simultaneously amounted to 12.2%. The results of the study partially show that work ethic has an effect on work productivity, Employee Management Information System (SIMPEG) has no effect on work productivity. Simultaneously work ethic and Employee Management Information System (SIMPEG) affect work productivity.